2018
DOI: 10.13005/ojc/340307
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of A Two-Step Method to Synthesize Azelaic Acid from Oleic Acid

Abstract: The present study deals with the oxidative cleavage of oleic acid (OA) using hydrogen peroxide and tungstic acid as a catalyst to produce azelaic acid. A two-step method has been expanded for the optimization of a new route of azelaic acid synthesis with the addition of sodium hypochlorite as the co-oxidation. The Central Composite Design (CCD) and Response Surface Methodology (RSM) were performed to optimize the production of azelaic acid. The interaction effect among catalyst concentration, substrate molar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…RSM is useful for modeling and analyzing problems, where the observed response is influenced by several variables and also aims to optimize the response. [21][22] A software package of Minitab version 17 was used in this study.…”
Section: Design Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…RSM is useful for modeling and analyzing problems, where the observed response is influenced by several variables and also aims to optimize the response. [21][22] A software package of Minitab version 17 was used in this study.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…The selection of variables range needs to be extremely precise in studies of RSM. [22][23] Results of the experimental design performed to achieve higher conversion are shown in The mutual interaction between stirring speed and catalyst concentration can be interpreted from the response contour plot diagram (Fig. -4), which indicated that that alkyl-diethanolamide production is related to both stirring speed and catalyst concentration.…”
Section: Mutual Effect Of Parametersmentioning
confidence: 99%
“…And at a temperature of 90 0 C and a catalyst concentration of 7%, 89.83% conversion was obtained. Because of the difficulty of determining an optimum value that will produce the maximum conversion, it is necessary to continue optimizing this process condition using the Response Surface Methodology 19,20 .…”
Section: Effect Of Reaction Temperaturementioning
confidence: 99%
“…[6][7][8][9] However, the toxicity and potential harm to humans limit their application. Some researchers turned to use hydrogen peroxide (H 2 O 2 ) as an oxidant for this reaction [10][11][12] as H 2 O 2 is environmentally benign and produces water as the only by-product. Some transition metal containing catalysts, [13][14][15][16] such as H 2 WO 4 @Al-MCM-41, 12 BaFeO 3Àd , 17,18 Ru(OH) x /g-Al 2 O 3 19 and VO@TiO 2 20 have been proved efficient in catalyzing this reaction with H 2 O 2 as oxidant.…”
Section: Introductionmentioning
confidence: 99%